FORMULATION AND EVALUATION OF NANOSTRUCTURED LIPID CARRIER FROM POMEGRANATE PEEL EXTRACT (PUNICA GRANATUM L.) AND ITS ANTIWRINKLE ACTIVITY TEST IN CREAM DOSAGE FORM - Diantinofriani
Ultra violet (UV) rays are the most important factor in the occurrence of skin aging. Continuous exposure to UV rays (photoaging) induces free radicals that cause various damage to the structure and layers of the skin. To minimize this damage, antiaging products that contain antioxidants can be used. Pomegranate peel (Punica granatum L.), has a high antioxidant content and has been used in various topical antioxidant products. Nanostructured Lipid Carrier (NLC) has many advantages in dermatological applications. In this study, the development of NLC formulas from pomegranate peel extract (PPE) and evaluation of its characteristics as well as tests of antioxidant, anti-wrinkle, and skin moisture activities were carried out. The NLC-PPE formula was developed using various solid lipids, liquid lipids and surfactants. The best formula was obtained from a formula consisting of cetyl alcohol, oleic acid, Tween 80, and pomegranate peel extract, with a particle size of 208.6 ± 5.48 nm; polydispersity index 0.322 ± 0.05; and zeta potential value -26.60 ± mV. NLC-PPE had antioxidant activity with an IC50 value of 12.34 ± 2.44 g/ml, and NLC-PPE cream had an IC50 value of 19.35 ± 4.04 g/ml. NLC-PPE cream does not irritate the skin or eyes, resulting in zero irritation score. Statistical results with two-ways ANOVA showed that there was a difference in the level of wrinkles and the value of trans epidermal water loss (TEWL) during the 4-weeks application period (p<0.05). There was no difference in the level of wrinkles or TEWL values between the tested NLC-PPE cream containing 1.6% PPE and 2% PPE cream (p>0.05).